ANALISIS KRITIK SOSIAL PADA FILM PENDEK BERJUDUL CAP-CIP TOP KARYA LUDY OJI PRATAMA - Mulia, Tamtu Ageng; Setyawan, Bagus Wahyu (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
The short film entitled Cap-Cip Top tells the story of the trade competition among mothers. The film contains a lot of social criticism about the spread of fake news and social criticism of young people who have low morale. The purposes of this research are (1) to describe the social criticism that appears in a short film entitled Cap-Cip Top, (2) to describe its relevance to learning Indonesian in senior high school. This study used descriptive qualitative method. The data collection technique used is note-taking technique. The source of the data in this study is a short film entitled Cap-Cip Top and sources of reference books, journals and articles. The results of this study are (1) 6 social criticisms that appear in a short film entitled Cap-Cip Top, (2) relevance to learning Indonesian in the 2013 Curriculum at the SMA level to be precise at KD 3.19 analyzing the content and language of plays or films read and heard . The social criticism contained in the film is useful for adding information to students about the problems that are happening in society.